Impacts of Climate Change on Korean Agriculture and Its Counterstrategies - 김창길 (한국농촌경제연구원, 2010)
The average temperature in Korea has increased by 1.5℃ over the last 100 years, the winter season has become shorter with a longer summer season, and the time for the blooming of spring flowers has become earlier due to global warning. As a result of these changes, agricultural productivity has decreased, the cultivation regions for crops have moved northward, and damages from winter pests has increased. Scientific diagnosis and evaluation of climate change is very important in setting a vision for future farming and the direction for agricultural policy. It will provide useful information for the establishment of countermeasures such as long-term regional agricultural development plans and farm household planning. This study was implemented in order to make recommendations for systematic and step-by-step countermeasures to climate change through in-depth analysis of climatic changes and their impacts on the agricultural sector. In order to accomplish the purpose of the study, this project was planned as a two-year task, and in 2008, the first year of the task, the study covered current status analysis and forecast of climate change; diagnosis of agricultural production pursuant to climate change; a review of cases for impact analysis in agricultural sector in major countries; and the ripple effect of climate change on the agricultural economy. In 2009, the general ripple effect of climate change was analyzed while suggesting a master plan to cope with climate change in the agricultural sector. This master plan was based on evaluations by analysts and experts. who prioritized various countermeasures to climate change both for major crop production regions and for individual farm household. This report consists of a general overview of the first and second year study. Chapter one presents the needs of the study, a summary of preceding studies, and methodology. Chapter two describes the current state and outlook for climate change at home and abroad. Chapter three covers basic concepts and theoretical approaches to cope with climate change in the agricultural sector. Chapter four reviews general impacts of climate change on the agricultural ecosystem, including the influence of climate factors, shifts in major production areas of crops, and economic impacts. Chapter five describes farmers' awareness of climate change, their attitudes to coping with climate change, and their decision-making regimes under risk and uncertainty. Chapter six presents impacts of climate change on the agricultural sector of major countries (Japan, the European Union, the United Kingdom, China, and Australia), and countermeasures in these respective countries. In Chapter seven, a basic direction of countermeasures to climate change is discussed along with the master plan for adaptation and related core tasks. Lastly in Chapter eight, a summary and conclusion are presented. The major findings of this study are summarized as follows : First, the National Institute of Meteorological Research (NIMR) forecasted that the average temperature will increase by 1.5℃ by 2020, 3.0℃ by 2050 and 5.0℃ by 2080 from the 30-year average between 1971~2000. They also forecasted that precipitation will increase by five percent by 2020, seven percent by 2050 and fifteen percent by 2080. Second, due to increases in temperature by global warming, the appropriate region for cultivation of certain crops is shifting and new kinds of pests are emerging, which are expected to result in changes to cultivated crop species and an increase in the area of crops damaged by these pests. In particular, apples, peaches, grapes and beans are expected to suffer more damage due to brown grasshoppers, and the areas susceptible to rice stripe virus (RSV) will move northward, expanding to a nationwide level. Third, the result of an analysis on climate variables by the kind of disaster which causes damage to crops shows that damages by typhoon, strong wind-blast, and snow have increased due to increases in annual average temperature, while damages by seismic wave, strong wind blast, storm and snow have increased due to an increase in pole temperature difference. The analysis also showed that as precipitation increased, the damage from heavy rain increased, whereas the damage from hail, lightning and strong wind-blast decreased. In addition, damage by heavy rain and typhoon has increased as the intensity of precipitation has increased. Fourth, the result of an analysis on the factors that have contributed to stagnant yield of rice in the periods of 2002~2003 and 2006~2007 showed that the 'weather' factor had a larger impact on the yield than the 'technology' factor. In the period of 2002~2003, weather had a contributing factor of 76.4 percent, whereas technology had a contributing factor of 23.6 percent. In the period of 2006~2007, weather had a contributing factor of 66.5 percent whereas technology had a contributing factor of 33.5 percent. In both periods, weather had a significantly bigger impact than technology. Fifth, a crop simulation analysis was used to check the influence of adaptation means to climate change, and the result of the analysis showed that as global warming progressed, the quantity of rice decreased when cultivation timing was fixed, regardless of the ecotype of rice plant, the quantity of nitrogenous fertilization, and irrigation condition. When cultivation timing was adjusted, the quantity of rice increased. This result implies that, at least in the case of agricultural sector, developing production technologies adapted to climate change can minimize potential risks. Sixth, the shifting of major production regions due to climate change was observed. In the case of apples, peaches, grapes and the 'Hallabong' citrus fruit, the cultivated regions moved northward while the cultivated regions for apple and grape expanded nationwide. And in the case of tropical crops, some of which are cultivated on Jeju Island, it was analyzed that it will be possible to cultivate a considerable number of tropical fruit items within a number of years. Seventh, for the analysis of climate change's effect on agricultural productivity, a Kernel regression was applied to four crops: rice, cabbage, radish and apple. The result of the regression analysis showed that, in the case of rice, the rise of temperature by 1℃ increased the production quantity by approximately 24.4kg per 10a when the average temperature during cultivation period is lower than 19℃ due to climate factors. When the average temperature is higher than 20℃, the production quantity fell by approximately 6.2kg per 10a. In the case of cabbage, radish and apple, the influence of climate factors to productivity varied by item and region. Eighth, for the analysis of climate change's influence on farming assets, a Ricardian model was applied, and according to the analysis, the price of farmland per ha decreased by 14.55~19.24 million won when annual average temperature (12.4℃) increased by 1℃. An analysis was conducted to identify climate change's influence on gross agricultural income by applying a Ricardian model, and the result of the analysis showed that the increase of temperature by 1℃ reduced gross agricultural income by 2.6~4 million won per ha, which is larger than the influence on farmland price. Ninth, the result of a survey showed that farmers' awareness of climate change appeared to be high and they felt unusual changes in weather and an increase in diseases and harmful insects. The survey result also showed that farmers had a keen interest in the countermeasures to climate change. They showed a high willingness to participate in the adaptation plan at the farmhouse level in the future, but there were bottlenecks such as lack of techniques and knowledge, insufficient information, and shortage of labor. Tenth, an Expectation Utility Model was used to analyze the benefits of adopting means for adapting to climate change for the period of 2011~2040. The difference of expected income depending on the application or non-application of means of adaptation was found, and the analysis showed that there will be an income difference of approximately 790 thousand won in Gwangju, 1.2 million won in Milyang and 1.4 million in Jeonju. The probability of farmers applying means of adaptation was indirectly calculated based on the model. According to the calculation, it is anticipated that approximately 65 pcrcent of farmers would adopt means of adaption. What this shows is that farmers are keenly interested in adapting to climate change and that their capability to accommodate appropriate technology is high. Lastly, the result of an evaluation on the priority of means of adaptation in agricultural sector revealed that development of technology and management of agricultural infrastructure are the most important. It showed improvement of plant breeding to be the first priority, management of water supply for agriculture as the second priority, and development of production technology as the third priority in all cases of short, medium and long-term planning. Up to now, the main focus of countermeasures to climate change in agricultural sector was given to the measures to mitigate greenhouse gas, but in consideration of the inevitability of global warming, and especially the weather-dependent characteristics of agriculture, more interest and policy-based support will have to be given to the measures for adaptation to climate change. Countermeasures to climate change in the agricultural sector are especially required to actively change perceptions on climate change and expand common understanding in order to minimize risk and utilize climate change risks as an opportunity. In order to accomplish this, appropriate education and training programs will have to be developed and operated for farmers, government officials, and people in charge of relevant organizations. In order to effectively implement the adaptation strategy in the agricultural sector, it is important to have roles appropriately assigned to the subjects concerned, such as government officials, farmers, research professionals and people in charge of relevant organizations, as well as establish an integrated administration system to comprehensively plan and drive countermeasures to climate change. In order to perform a systematic study of climate change's impact on agriculture and prepare countermeasures, it will be important to organize joint research among relevant sciences, including: agricultural science, ecology, agricultural engineering, hydrology, meteorology and agricultural economics. To ensure higher reliability of the analysis, an integrated simulation model, which connects the scenario-based forecast with the characteristics of agriculture and socio-economic factors, has to be developed continuously. On top of that, future study will have to perform more concrete and systematic analysis of economic and policy effects expected from utilizing different means of adaptation in the agricultural sector. Researchers: Chang-Gil Kim, Sang-Min Lee, Hak-Kyun Jeong, Jeong-Kyung Jang, Yoon-Hyung Kim and Chung-Kuen Lee E-mail address: changgil@krei.re.kr
Keywords: 기후변화; 농업정책; 한국